Thermal Comfort in Different Types of Buildings: A review study - Elaiab, Dr. Fatima (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The paper presents a literature review of thermal comfort on buildings in different sectors. Main factors affecting thermal comfort will be discussed. Heat loss and gain through buildings will be highlighted which is responsible for the state condition of the users in different types of buildings. In addition, focus on the effect of building’s function on thermal comfort.